Determinants of utilization of antenatal care services in Benishangul Gumuz Region, Western Ethiopia: a study based on demographic and health survey - Kassahun Tiruaynet; Kindie Fentahun Muchie (BMC, 2019)
Abstract Background Utilization of antenatal care (ANC) in Ethiopia was low. There was also a variation of this underutilization of ANC service from region to region in the country. Therefore, this study aimed at providing a comprehensive analysis on socio-economic and demographic determinants of utilizing ANC services in Benishangul Gumuz Region. Methods The study was conducted based on the 2011 Ethiopian Demographic and Health Survey. Data analyzed were taken from 674 mothers in Benishangul Gumuz Region who had at least one child in the 5 years before the survey was undertaken. Binary logistic regression model was used to analyze the data. Variables with a p-value< 0.25 in bivariable analysis were considered for the final model. In the final multivariable model, a variable was declared as significantly associated with ANC utilization for p-value< 0.05. Adjusted odds ratio with its respective 95% confidence interval was reported to show the strength of association. Results The results of the study showed that educational level, place of residence, ethnicity, and household's wealth were determinants of ANC utilization in the region at 5% level of significance. Conclusion Lower educational level, difference of ethnicity, lower wealth status and rural residence of women were determinants on ANC utilization. Providing awareness creation on ANC visits for rural women during health care services provision, at community meeting, at working place and at any social association were recommended. In addition, creating conducive environment in entrepreneurial activities for poor women would improve ANC utilization. Lastly, further researches were recommended to study the effect of various traditional, cultural and other related practices on utilization of ANC services among ethnic groups in the region.